Avaliação pós-ocupação do núcleo habitacional Santa Marta - SM - Jacques, Cláudio Antunes (2008)
This work has as a main objective to perform a Post-Occupancy Evaluation of the Housing Nucleus of Saint Marta (COHAB - Santa Marta), after twenty eight years of its implantation, comprehending two approaches. The first one evaluated the level of satisfaction of the users through a detailed questionnaire that pointed positive and negative aspects, emphasizing the deficient quality of some components of the housing units that presented deterioration within a short period of existence. As a consequence, court processes were judged to the reparation of the insurance prizes in almost six hundred houses, from the total of eight hundred and seventy two. The second approach was the technical evaluation of the project and of the found pathologies. The conclusion points to a project with housing area and internal dimensions smaller than the necessity of the users, and to little pathologies resultant to the residents intervention. As a positive aspect, the adopted constructive system - hollow bricks masonry reinforced with concrete braces - resulted in constructive stability throughout the dwellings existence. It was also detected the evolution of the land division, which is being directed to the decharacterization of the initial aesthetics, with the execution of reforms and increases in constructions, according to the demand of the families and the real estate market dynamics. Was included suggestions to enlargement in units of two and three bedrooms, and to futures projects.